Instant Autodesk AutoCAD 2014 customization with .NET : use AutoCAD's .NET API to create your own powerful, custom applications for AutoCAD /: use AutoCAD's .NET API to create your own powerful, custom applications for AutoCAD. (2013) - Unknown
No abstract available